Enhanced mechanical performance of cellulose nanocrystal doped eco-friendly calcium-alginate based bio-composite fiber with superior flame retardancy. Issue 11 (June 2022) - Zhang, Xiaolin; Yang, Jin; Weng, Lin; Fan, Wei; Xu, Yanyan
Petroleum-based polymer fire-resistant fabric is not considered as eco-friendly, and has other problems like heavy weight and irritating tickling. On the other hand, even though Ca–alginate fiber is a natural fire-resistant polysaccharide derivative, its low tensile strength prevents the fiber from being a potential fire-resistant material. To enhance its mechanical performance, cellulose nanocrystal (CNC) functioned as reinforced nanofiller, assisted by a small amount of propanol to improve CNC dispersion in solution. CNC-doped alginate fiber (pC–Alg) was fabricated by the microfluidic spinning technique, and the effects of CNC content and the drawing ratio on the fibrous mechanical performance were investigated. Comparative studies indicated that a combination of 0.50 wt.% CNC, 6.00 v.% propanol, and 1.6 draft ratio helped pC–Alg fiber to achieve outstanding breaking strength of around 2.00 cN/dtex. It was shown that the use of propanol solvent and the incorporation of CNC can effectively eliminate CNC aggregation and reach a three-fold better tensile performance than the control. Limiting oxygen index test also showed that the resultant hybrid pC–Alg fiber still displayed good flame retardancy, making it an ideal candidate for fire-protection clothing.